The Existential Hope for Love in Sheerwood Anderson's The Dumb Man - Mohammed, Khaled Ahmed; Setiadi, Kostavialdus; Pasopati, Rommel Utungga; Firda, Erlis Hersetya; Ramadhani, Riska Dewi; Margaretha, Sherlly (PT. Gudang Pustaka Cendekia, 2024)
The research takes an insight look into the complicated representation of love, using the short story of The Dumb Man by Sherwood Anderson within the existentialism framework. The deaf and mute protagonist becomes a metaphor for the universal human condition in his search for love and communication amidst a society that cares less. In his tacit quest for love, Anderson exemplifies an existentialist perspective: Love is not a desire—one feels—but a highly conscious effort to assert one's existence in reality, both freely chosen and constrained by society. This analysis is conducted through qualitative method and explorative approach in unpacking meaning from the narrative, with the contention that hopes for love functions as a central vehicle for self-transformation. It is in this quest for love that this story wrestles through the tension of aloneness with man's need to connect, representative of the complex, intertwined relationship between individual independence and the world outside. Ultimately, through this story, how it unfolds existentialism culminates into the relentless, sometimes painful pursuit of love—thereby bringing out the core role of existentialism in the journey towards self-actualization and insight into the human condition.